2021
DOI: 10.1177/00368504211039615
|View full text |Cite
|
Sign up to set email alerts
|

Simulation research on the protection performance of fall protection net at the end of truck escape ramp

Abstract: Introduction: Although the fall protection net installed at the end of the truck escape ramp has a protective effect on trucks and drivers, but lacks sufficient theoretical basis and verification method. Objectives: The primary objective of this paper was to design a fall protection net that meets the regulations and research its protection performance. Methods: The finite-element method was used to design the overall size, material, mesh length, mesh type, shape, and supporting structure of the fall protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…When the time reached 0.6 s, the third net started to intercept, while the first 2 nets still continued to elongate, thus playing a concerted role in interception until the vehicle had been successfully intercepted. Other studies on the change in rope force can be found in Qin et al [20], Yan et al [21], and Ma et al [22]. Unfortunately, the acceleration reached 417 m/s 2 , far beyond the maximum acceleration suitable for human limits.…”
Section: Determination Of Parameters Of the Arresting Netmentioning
confidence: 99%
“…When the time reached 0.6 s, the third net started to intercept, while the first 2 nets still continued to elongate, thus playing a concerted role in interception until the vehicle had been successfully intercepted. Other studies on the change in rope force can be found in Qin et al [20], Yan et al [21], and Ma et al [22]. Unfortunately, the acceleration reached 417 m/s 2 , far beyond the maximum acceleration suitable for human limits.…”
Section: Determination Of Parameters Of the Arresting Netmentioning
confidence: 99%